Upper Gastrointestinal Bleeding from Gastric Amyloidosis in a Patient with Smoldering Multiple Myeloma - Mihajlo Gjeorgjievski; Treta Purohit; Mitual B. Amin; Paul J. Kurtin; Mitchell S. Cappell (Case Reports in Gastrointestinal Medicine)
Amyloidosis is a common complication of patients with monoclonal gammopathy of undetermined significance (MGUS), smoldering multiple myeloma (SMM), and multiple myeloma (MM). This proteinaceous material can be deposited intercellularly in any organ system, including the gastrointestinal (GI) tract. In the GI tract, amyloidosis affects the duodenum most commonly, followed by the stomach and colorectum. Gastric amyloidosis causes symptoms of nausea, vomiting, early satiety, abdominal pain, and GI bleeding. A case of upper GI bleeding from gastric amyloidosis is presented in a patient with SMM. Esophagogastroduodenoscopy (EGD) revealed a gastric mass. Endoscopic biopsies revealed amyloid deposition in the lamina propria, consistent with gastric amyloidosis. Liquid chromatography tandem mass spectrometry performed on peptides extracted from Congo red-positive microdissected areas of paraffin-embedded stomach specimens revealed a peptide profile consistent with AL- (lambda-) type amyloidosis. Based on this and multiple other case reports, we recommend that patients with GI bleeding and MGUS, SMM, or MM undergo EGD and pathologic examination of endoscopic biopsies of identified lesions using Congo red stains for amyloidosis for early diagnosis and treatment.